2013
DOI: 10.5812/numonthly.8733
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Aspirin on Double Lumen Permanent Catheter Efficacy in ESRD

Abstract: BackgroundThe complications of vascular access are the most imperative etiology for hospitalization, morbidity and mortality in chronic hemodialysis. The most prevalent complication of central catheter is dysfunction due to thrombosis. Aspirin is an anti-aggregative platelet drug that may increase the patency of permanent catheters (perm-cath).ObjectivesThe aim of this study was to evaluate the role of Aspirin in perm-cath survival.Patients and MethodsThis study included a total of 185 ESRD cases according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…In a study which was conducted by Mozafar et al, on the efficiency of aspirin on double lumen permanent catheter efficacy in endstage kidney failure on 180 patients with end-stage renal disease who were divided into two groups-control and intervention, the mean of catheter survival in two groups were compared. The average age of patients in this study was 71.1 which was almost equal to the present study (11). In the treatment group with aspirin, the mean survival time in the group was significantly higher than the control group (5.3 ± 4.7 years versus 3.9 ± 2.7 years; P = 0.012), which could be related to the significant positive effect of aspirin in our study as well.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In a study which was conducted by Mozafar et al, on the efficiency of aspirin on double lumen permanent catheter efficacy in endstage kidney failure on 180 patients with end-stage renal disease who were divided into two groups-control and intervention, the mean of catheter survival in two groups were compared. The average age of patients in this study was 71.1 which was almost equal to the present study (11). In the treatment group with aspirin, the mean survival time in the group was significantly higher than the control group (5.3 ± 4.7 years versus 3.9 ± 2.7 years; P = 0.012), which could be related to the significant positive effect of aspirin in our study as well.…”
Section: Discussionsupporting
confidence: 66%
“…The most important reason for their failure is the formation of clots, while its cause is not well-known (9). Recent studies have shown that aspirin not only acts as an antiplatelet, but also causes diminishing oxidative stress and inflammation (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Shaffer et al reported a primary patency of 35% in the 1-year follow-up. In addition, Mozafar et al reported the mean survival of catheter to be 5.3 ± 4.7 months in the aspirin group (5). In our study, the survival rate of permcath at 4 and 5 months of follow-up was higher in the Clopidogrel group, compared to the placebo group.…”
Section: Discussionsupporting
confidence: 49%
“…VA complications are the most important causes of hospitalization and morbidity in end-stage renal disease patients. Success of hemodialysis depends on the patency and function of permanent catheter (permcath) (5). On the other hand, thrombosis is the most common complication of VA and permcath insertion for hemodialysis (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation